(untitled) (Revista Contexto & Saúde, 2026)
Objective: to identify the risk factors associated with hospitalizations and the mortality rate due to SARS during the COVID-19 pandemic in a health region of Rio Grande do Sul. Method: Cross-sectional study carried out with data from the Information System of the Epidemiological Surveillance of Influenza of the Ministry of Health in the period from January 2020 to August 2021. The outcomes "hospitalizations due to SARS" and "mortality due to SARS" were analyzed, as well as sociodemographic and health variables for association analysis. Descriptive analysis and Cox’s proportional risk model were performed to calculate the risk ratio and 95% confidence interval. Results: The prevalence of individuals hospitalized with SARS and at least one risk factor for COVID-19 was 61.0% and was higher among females, age 40 years or older and among individuals with low education. The mortality rate among those hospitalized with SARS due to COVID-19 was 10.4/1,000 and was higher among individuals of black, brown, yellow and indigenous color, with low education, and with presence of one or more risk factors for COVID-19. Conclusion: The social determination of health is explicit in this study and became more evident with the presence of a sanitary and humanitarian crisis such as COVID-19.